Oxidative stress induced by berberine-based mitochondria-targeted low temperature photothermal therapy - Hu, Hongzhi; Song, Qingcheng; Yang, Wenbo; Zeng, Qianwen; Liang, Zihui; Liu, Weijian; Shao, Zengwu; Zhang, Yiran; Chen, Chao; Wang, Baichuan (Frontiers in Chemistry, 2023)
Introduction: Mitochondria-targeted low-temperature photothermal therapy (LPTT) is a promising strategy that could maximize anticancer effects and overcome tumor thermal resistance. However, the successful synthesis of mitochondria-targeted nanodrug delivery system for LPTT still faces diverse challenges, such as laborious preparations processes, low drug-loading, and significant systemic toxicity from the carriers. Methods: In this study, we used the tumor-targeting folic acid (FA) and mitochondria-targeting berberine (BBR) derivatives (BD) co-modified polyethylene glycol (PEG)-decorated graphene oxide (GO) to synthesize a novel mitochondria-targeting nanocomposite (GO-PEG-FA/BD), which can effectively accumulate in mitochondria of the osteosarcoma (OS) cells and achieve enhanced mitochondria-targeted LPTT effects with minimal cell toxicity. The mitochondria-targeted LPTT effects were validated both in vitro and vivo. Results:In vitro experiments, the nanocomposites (GO-PEG-FA/BD) could eliminate membrane potential (ΔΨm), deprive the ATP of cancer cells, and increase the levels of reactive oxygen species (ROS), which ultimately induce oxidative stress damage. Furthermore, in vivo results showed that the enhanced mitochondria-targeted LPTT could exert an excellent anti-cancer effect with minimal toxicity. Discussion: Taken together, this study provides a practicable strategy to develop an ingenious nanoplatform for cancer synergetic therapy via mitochondria-targeted LPTT, which hold enormous potential for future clinical translation.